Stygobiotic isopod Stenasellus sp. in Sarongge Jompong cave, Tasikmalaya karst area, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kurniawan ID, Rahmadi C, Akbar RTM, Prakarsa TBP. 2022. Stygobiotic isopod Stenasellus sp. in Sarongge Jompong cave, Tasikmalaya karst area, Indonesia. Biodiversitas 23: 1495-1504. Stenasellus, a stygobiotic isopod, was first reported in Tasikmalaya karst by local cavers in 2018 in Sarongge Jompong Cave. This study aimed to investigate the population, activities, and habitat characteristics of Stenasellus sp. in Sarongge Jompong, Tasikmalaya karst area, Indonesia. Population and activities were recorded through direct intuitive search. We measured several important physicochemical parameters to study habitat characteristics. Statistical analyses-namely Non-metric Multi-dimensional Scaling and Detrended Correspondence Analysis-were conducted to understand the difference in water characteristics among microhabitats and the relation between water characteristics and population size. The results showed that the population was distributed in 4 microhabitats with the maximum observed individuals of 8. Several activities were successfully monitored, including crawling, resting, hiding in crevices, and moving to different locations through the water. All microhabitats were wet gours connected to small water currents located in the dark zone of the cave passage. Water characteristics of microhabitat site 1 were more similar to site 2 and the numbers of individuals in these sites were larger than sites 3 and 4. Among water parameters, resistivity showed the most robust relation with Stenasellus population in which both variables were positively correlated. This correlation indicated that Stenasellus sp. preferred microhabitats with less contamination. Intrinsic and extrinsic factors may potentially threaten the population. The potential threats and conservation challenges need to be identified and mitigated to reduce the risk of biodiversity loss to these isopods, mainly due to their small population size, specific microhabitat, and susceptibility to disturbance. Considering these factors, research on taxonomy will be essential for conservation efforts.
Keywords: Conservation, microhabitat, physicochemical parameter, population, stygobiont